Coinfection of Porphyromonas gingivalis and Toxoplasma gondii impairs neurocognitive function and induces anxiety-like behavior in rats: a behavioral study - Cao, Henglong; Lin, Jianfeng; Wei, Wanyi; Luo, Jianzhao; Yuan, Hao; Song, Yining; Yang, Kunmei; Ma, Xiao; Song, Ning; Yu, Miao (Frontiers in Immunology, 2026)
Toxoplasma gondii (T. gondii) is a ubiquitous protozoan parasite that can infect a wide range of hosts, including humans and rodents. Dental plaque microbiota serves as the initiating factor in periodontal diseases, with Porphyromonas gingivalis (P. gingivalis) being the principal pathogenic bacterium. Recent studies have suggested a potential link between T. gondii infection, periodontal diseases and neuropsychiatric disorders, although the underlying mechanisms remain unclear. This study aimed to investigate the effects of T. gondii infection on cognitive function and anxiety-like behavior in rats with periodontitis, using a series of behavioral tests, including the Morris water maze, open field test, novel object recognition test, Y-maze test, and elevated plus maze test. We explored whether coinfection of P. gingivalis and T. gondii could impair spatial learning and memory and induce anxiety-like behavior in rats. Our results showed that coinfection of P. gingivalis and T. gondii significantly increased anxiety-like behavior and reduced cognitive function in rats. These findings suggest that the coinfection may disrupt central nervous system (CNS) function, providing new insights into the association between T. gondii infection, periodontitis, and neuropsychiatric comorbidities. Future research should focus on elucidating the molecular mechanisms underlying these effects and exploring potential therapeutic strategies to mitigate the impact of T. gondii infection and periodontal diseases on mental health.